Development and validation of analytical methodology for the quantification of aldehydes in e-cigarette aerosols using UHPLC-UV. (June 2018) - El Mubarak, Mohamed A.; Danika, Charikleia; Vlachos, Nikolaos S.; Farsalinos, Konstantinos; Poulas, Konstantinos; Sivolapenko, Gregory
Abstract: Aldehydes are produced in e-cigarette aerosols, as a result of the thermal decomposition of vegetable glycerin, propylene glycerol and flavorings in the atomizer. These aldehydes were collected with derivatization into 2, 4-dinitrophenylhydrazine using impinger trapping. A new methodology for simultaneous quantitative analysis of aldehydes in base liquids was developed and validated. Chromatographic separation was carried out on a Jupiter Proteo 90A column, with the mobile phase consisting of 0.1% formic acid in water and acetonitrile, at a flow rate of 0.4 mL/min. Linearity was demonstrated over the range of concentrations 0.025-10 μg/mL, with correlation of determination ≥ 0.999. Intra- and inter-day % relative standard deviation and relative error were ≤ 10%. The lower limit of detection and quantification were 0.008 and 0.025 μg/mL, respectively. This method was further used for the quantification of aldehydes emitted by different base liquids. It has been shown that vegetable glycerin produces the highest percentage of aldehydes after thermal decomposition compared to propylene glycerol. We propose that it can be used for future e-liquids emissions studies. Highlights: UHPLC method was developed for determination of aldehyde in base liquids. Chromatographic separation was carried out on a Jupiter Proteo column. A gradient elution for analysis of the analytes was developed. Sensitivity, accuracy, precision and stability were established for validation.